Transformasi Ekonomi Desa Melalui Koperasi Merah Putih: Kajian Persepsi Masyarakat di Youtube - Suyitno Suyitno; Rokhimah Rokhimah; Erna Nur Faizah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – The Koperasi Merah Putih Program aims to strengthen the people's economy in villages by empowering the community through cooperatives that can create jobs, improve welfare, and reduce dependence on large markets. However, the major challenge faced is the often lack of transparency in the management of cooperatives, as well as the potential misuse of funds that can undermine the program's objectives. This research aims to explore the public's perception of the Koperasi Merah Putih as an instrument of economic empowerment at the village level, as well as assess the challenges faced by cooperatives in achieving their goals. Aim – This study aims to: (1) analyze public perceptions of the role of the Koperasi Merah Putih in strengthening the people's economy, (2) identify challenges in cooperative management, including transparency issues and potential corruption, (3) explore the role of cooperatives in the empowerment of women and marginalized groups, and (4) provide recommendations to improve the effectiveness of cooperatives in the economic empowerment of rural communities. Design / methodology / approach – This study uses a qualitative approach with content analysis. The data was obtained from comments on the YouTube platform related to the Koperasi Merah Putih. The comments were selected based on their relevance to the themes of economic empowerment, cooperative management challenges, and transparency. Thematic analysis techniques are used to identify key themes from the collected data. Findings – The findings show that despite many positive expectations for cooperatives, the public is concerned about the potential misuse of funds and non-transparent management. Cooperatives are also expected to be a means of empowering women and marginalized groups, but there are still challenges related to the inadequate capacity of cooperative administrators. Conclusion – The Koperasi Merah Putih has great potential in strengthening the people's economy, but it requires transparent management and training for administrators to ensure its success. Efficient and accountable management will encourage active participation from the community, increase member trust, and ensure that the cooperative's goals can be achieved in a sustainable manner. Research implication – This study suggests the need for a more stringent monitoring system and ongoing training for cooperative managers to increase the effectiveness of these programs. Independent supervision and structured training will ensure transparent, accountable, and supportive management of the cooperative in facing operational challenges and improving managerial skills consistently and professionally. Limitations – The study was limited to secondary data from YouTube comments, which may not be representative of the views of the entire rural community. Further research with primary data collection methods is needed to dig into a more comprehensive perspective.